2019
DOI: 10.3389/fpsyg.2019.02194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Self-Relevance and Reputational Concerns on Altruistic Moral Decision Making

Abstract: Complex moral decision making may share certain cognitive mechanisms with economic decision making under risk situations. However, it is little known how people weigh gains and losses between self and others during moral decision making under risk situations. The current study adopted the dilemma scenario-priming paradigm to examine how self-relevance and reputational concerns influenced moral decision making. Participants were asked to decide whether they were willing to sacrifice their own interests to help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
(99 reference statements)
2
8
0
Order By: Relevance
“…A considerable body of empirical and theoretical research has examined how different kinds of cost/benefit trade-offs have evolved to influence and generate pro-social and altruistic behaviours (de Waal, 2008d;Fehr and Camerer, 2007;Fehr and Fischbacher, 2003;Kitcher, 1993;Kurzban et al, 2013). This include studies of prosocial behaviours involving monetary losses (Berg et al, 1995;Forsythe et al, 1994;Guth et al, 1983;Kahneman et al, 1986;Nash, 1950), physical pain (Crockett et al, 2014;Hein et al, 2010;Volz et al, 2017) or social punishments linked and reputational motivations (Roberts, 1998;Zhan et al, 2019) while acting in order to obtain a benefit or prevent a loss for another person. Incurring these costs may be important, because they increase fitness by strengthening social ties.…”
Section: Weighing Effort Costs Against Rewarding Benefits In Social Interactionsmentioning
confidence: 99%
“…A considerable body of empirical and theoretical research has examined how different kinds of cost/benefit trade-offs have evolved to influence and generate pro-social and altruistic behaviours (de Waal, 2008d;Fehr and Camerer, 2007;Fehr and Fischbacher, 2003;Kitcher, 1993;Kurzban et al, 2013). This include studies of prosocial behaviours involving monetary losses (Berg et al, 1995;Forsythe et al, 1994;Guth et al, 1983;Kahneman et al, 1986;Nash, 1950), physical pain (Crockett et al, 2014;Hein et al, 2010;Volz et al, 2017) or social punishments linked and reputational motivations (Roberts, 1998;Zhan et al, 2019) while acting in order to obtain a benefit or prevent a loss for another person. Incurring these costs may be important, because they increase fitness by strengthening social ties.…”
Section: Weighing Effort Costs Against Rewarding Benefits In Social Interactionsmentioning
confidence: 99%
“…The findings confirmed that, facing the current crisis, the anger and grief produced by the members of the stigmatized group have a certain role in promoting their mutual help. In addition, perceived relevance also promotes the altruistic tendency, with supportive evidence for H5, verifying the promoting altruism effect of relevance perception in social identity (Gintis, 2000 ; Boyd et al, 2003 ; Zhan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 66%
“…Through this group identity, individuals have a connection with the group, and the consciousness of belonging to a group will strongly affect our perceptions, attitudes, and behavior (Tajfel and Turner, 1979 ). In groups, people cooperate extensively with non-relative members (Gintis, 2000 ; Boyd et al, 2003 ), and perceived self-correlation will affect people's altruistic help choices, decision-making time, and subjective negative emotional responses (Zhan et al, 2019 ). Thus, we hypothesize that:…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…In contrast, this altruistic tendency was larger toward strangers than friends. Compared with strangers, previous studies supposed that friends would be regarded as core components of the self and that individuals’ mental representations and behavior patterns toward friends were similar to those toward the self to a certain extent (Fan et al., 2013; Ma & Han, 2011; Northoff et al., 2009; Zhan et al., 2016, 2019; Zhu & Han, 2008). Thus, in our study, participants were indeed more willing to give up monetary gains to reduce the painful electric shocks for strangers than for themselves or friends.…”
Section: Discussionmentioning
confidence: 99%